2020
DOI: 10.1016/j.sste.2020.100362
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 and vit-d: Disease mortality negatively correlates with sunlight exposure

Abstract: The novel COVID-19 disease is a contagious acute respiratory infectious disease whose causative agent has been demonstrated to be a new virus of the coronavirus family, SARS-CoV-2. Alike with other coronaviruses, some studies show a COVID-19 neurotropism, inducing de-myelination lesions as encountered in Guillain-Barré syndrome. In particular, an Italian report concluded that there is a significant vitamin D deficiency in COVID-19 infected patients. In the current study, we applied a Pear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 11 publications
1
21
0
1
Order By: Relevance
“…Benefits for the UVB component of sunlight have also been reported, in which a negative association between the UV Index and COVID-19 deaths were observed in data from 152 countries using modeling that considered other potential effects of local weather (e.g., temperature, humidity) across January–May 2020 ( 49 ). Beneficial inverse associations between COVID-19 severity or death and local ambient UV levels or annual mean sunlight hours were also observed in Spain ( 50 ) and France ( 51 ), respectively, although this French study has been critiqued for the statistical approach undertaken ( 52 ). However, GDP and body mass index, but not mean UV Index (measured across November 2019–April 2020) were significant predictors of COVID-19 deaths (per million) in a multivariate regression analysis across the world ( 53 ).…”
Section: Uv Light Sun Exposure and Covid-19mentioning
confidence: 89%
“…Benefits for the UVB component of sunlight have also been reported, in which a negative association between the UV Index and COVID-19 deaths were observed in data from 152 countries using modeling that considered other potential effects of local weather (e.g., temperature, humidity) across January–May 2020 ( 49 ). Beneficial inverse associations between COVID-19 severity or death and local ambient UV levels or annual mean sunlight hours were also observed in Spain ( 50 ) and France ( 51 ), respectively, although this French study has been critiqued for the statistical approach undertaken ( 52 ). However, GDP and body mass index, but not mean UV Index (measured across November 2019–April 2020) were significant predictors of COVID-19 deaths (per million) in a multivariate regression analysis across the world ( 53 ).…”
Section: Uv Light Sun Exposure and Covid-19mentioning
confidence: 89%
“…Vitamin D Improving the physical barriers of the body by regulating the production of proteins for tight junctions [50], adherens junctions [51], and gap junctions [52] Stimulating the production of antimicrobial peptides, such as cathelicidin and defensins [55] Modulating T helper (Th) cell responses to induce a shift from Th1 to Th2 responses [61,62,64] Preventing cytokine storms by decreasing inflammatory cytokines [67,68] and nuclear factor κB (NF-κB) activation [69] Inverse correlation between vitamin D level and viral respiratory tract infection [38][39][40] Vitamin D deficiency/insufficiency observed in patients with COVID-19 [41] Inverse correlation between COVID-19 mortality and sunlight exposure [45] or vitamin D level [43,48] Worse prognosis in COVID-19 patients with a low level of vitamin D [47,49] Selenium Preventing mutations in viral genome [71][72][73] Increasing CD4 + T cell activation, proliferation, and differentiation; inducing Th1 phenotype [74] Enhancing the function of cytotoxic effector cells by increasing the cytotoxicity of CD8 + T cells and lytic activity of natural killer (NK) cells [77] Maintaining T cell maturation and functions, including T cell-dependent antibody production [79,80] Preventing vasoconstriction and blood coagulation [87], which may increase COVID-19 mortality [81] Higher selenium level in surviving COVID-19 patients compared to deceased patients [16] Higher recovery rate from COVID-19 in patients with higher selenium levels [17] Author Contributions: Conceptualization: H.K. ; investigation, writing, and original draft preparation: M.B.…”
Section: Consequences Of Deficiency/effects Of Supplementation In Infmentioning
confidence: 99%
“…The prevalence rate of COVID-19 and the rate of related deaths were significantly higher in high-latitude states (latitude ≥ 37°) than in low-latitude states (latitude < 37°) in the United States [ 42 ]. The average annual hours of sunlight exposure was negatively correlated with COVID-19 mortality [ 45 ]. It has also been suggested that vitamin D deficiency (serum 25-hydroxy vitamin D level of 20 ng/mL or lower) and insufficiency (serum 25-hydroxy vitamin D level of 21 to 29 ng/mL) are associated with increased mortality in COVID-19 in Indonesia [ 43 ].…”
Section: Micronutrients and The Immune Systemmentioning
confidence: 99%
“…L’équipe de Édouard Lansiaux a cherché à analyser la relation entre l’ensoleillement et le risque de décès chez les personnes ayant contracté la Covid-19 [10] . Cette étude, bien qu’observationnelle descriptive, a le mérite d’inclure un grand nombre de sujets.…”
Section: Vitamine D Et Covid-19unclassified